The Dual Roles of the Sandwich Generation in the Modern Era: Balancing Work, Family, and Mental Health - Ratu Khairulnisa; Yani Achdiani; Sarah Nurul Fatimah (AMK : Abdi Masyarakat UIKA, 2026)
The phenomenon of the sandwich generation has become an increasingly visible social reality in the modern era, particularly as individuals face simultaneous responsibilities toward their aging parents and their dependent children. This dual burden places individuals in a unique socio-economic and emotional position where financial obligations, caregiving duties, and professional demands intersect. This study analyzes the multidimensional roles, challenges, and coping strategies experienced by the sandwich generation in navigating work, family, and mental well-being. The research highlights contributing factors such as rising living costs, increasing life expectancy, insufficient financial planning across generations, and strong cultural expectations of filial duty. Findings show that sandwich generation individuals often experience chronic stress, emotional fatigue, and role conflict due to overlapping responsibilities. However, effective time management, social support systems, self-care practices, and the utilization of digital tools can help mitigate the psychological strain. This study emphasizes the necessity of structural support both within families and through workplace policies to promote mental health and enhance resilience among the sandwich generation. Ultimately, strengthening awareness about intergenerational financial literacy, caregiving readiness, and mental-health preservation is crucial in reducing the long-term burden faced by this demographic group.